A Microneedle Patch for Measles and Rubella Vaccination Is Immunogenic and Protective in Infant Rhesus Macaques - Joyce, Jessica C (J Infect Dis, 2018)
BACKGROUND: New methods to increase measles and rubella (MR) vaccination coverage are needed to achieve global and regional MR elimination goals. METHODS: Here, we developed microneedle (MN) patches designed to administer MR vaccine by minimally trained personnel, leave no biohazardous sharps waste, remove the need for vaccine reconstitution, and provide thermostability outside the cold chain. This study evaluated the immunogenicity of MN patches delivering MR vaccine to infant rhesus macaques. RESULTS: Protective titers of measles neutralizing antibodies (>120 mIU/mL) were detected in 100% of macaques in the MN group and 75% of macaques in the subcutaneous (SC) injection group. Rubella neutralizing antibody titers were >10 IU/mL for all groups. All macaques in the MN group were protected from challenge with wild-type measles virus, whereas 75% were protected in the SC group. However, vaccination by the MN or SC route was unable to generate protective immune responses to measles in infant macaques pretreated with measles immunoglobulin to simulate maternal antibody. CONCLUSIONS: These results show, for the first time, that MR vaccine delivered by MN patch generated protective titers of neutralizing antibodies to both measles and rubella in infant rhesus macaques and afforded complete protection from measles virus challenge.